2019
DOI: 10.4103/ijo.ijo_1494_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations and comparative outcomes of primary versus deferred intraocular lens explantation in delayed-onset endophthalmitis

Abstract: Purpose: To describe clinical presentations and comparative outcomes of primary versus deferred intraocular lens (IOL) explantation in delayed-onset endophthalmitis. Methods: In this retrospective study, a total of 77 eyes of 77 patients that were diagnosed clinically as delayed-onset endophthalmitis and underwent IOL explantation from January 1990 to January 2018 were included undiluted vitreous biopsy and IOL were subjected to microbiologic evaluation. Duration of sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In a recent previously published study of ours, we described the comparative outcomes of primary versus deferred IOL explantation in delayed onset low grade endophthalmitis. 14 In that study, we concluded that primary IOL explantation group required significantly fewer numbers of repeat intravitreal interventions compared to the deferred IOL explantation group. Additionally, the complication rates in terms of corneal decompensation or retinal detachment were comparable in the two groups.…”
Section: Discussionmentioning
confidence: 84%
“…In a recent previously published study of ours, we described the comparative outcomes of primary versus deferred IOL explantation in delayed onset low grade endophthalmitis. 14 In that study, we concluded that primary IOL explantation group required significantly fewer numbers of repeat intravitreal interventions compared to the deferred IOL explantation group. Additionally, the complication rates in terms of corneal decompensation or retinal detachment were comparable in the two groups.…”
Section: Discussionmentioning
confidence: 84%
“…The reported incidence of infectious endophthalmitis following open globe injuries ranges from 3.1% to 11.9% of open globe injuries in the absence of an intraocular foreign body (IOFB) [47][48][49][50][51][52]. The incidence increases from 3.8% to 48.1%, in the presence of an IOFB, with higher infection rates with retained IOFBs contaminated with organic matter from a rural setting [53][54][55][56][57].…”
Section: Post-traumatic Infectious Endophthalmitismentioning
confidence: 99%
“…[ 37 ] In recalcitrant cases of post cataract surgery fungal endophthalmitis, the intraocular lens explantation along with the lens capsule could benefit. [ 38 ] The visual outcome of fungal endophthalmitis is poorer than bacterial endophthalmitis.…”
Section: Current Knowledgementioning
confidence: 99%